PEMAHAMAN TRI NGA DAN PEMAHAMAN TRI N TERHADAP MINAT BERWIRAUSAHA - Dewi Kusuma Wardani; Laudiya Agnes Sikteubun (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
The purpose of this study was to examine the influence of understanding of the Tri-Nga and understanding of the Tri-N on the interest in entrepreneurship. This research methode is a snowball sampling survey with a quantitave approach. Data collection using a questionnaire. used in this study is multiple regression analysis Entrepreneurs have an important role in a country economy, this is because the presence and role of entrepreneurs greatly influences various aspects, especially aspects of life and society and economy. For this reason students are directed to take part in the entrepreneurship programs in order to foster entrepreneurial concentration. The results of this study indicatte that understanding of the Tri-Nga and unerstanding of the Tri-N affect the interest in entrepreneurship.